Development of portable solar power supply - Ahmad Marzuqi Farhan bin Jaafar (Department of Electronic Engineering Technology, Faculty of Engineering Technology, University Malaysia Perlis, 2015)
Development of solar power supply project is an upgrade to standard power supply which extended its input source from single input into dual input sources, the sources are source from supplier (Tenaga Nasional Berhad) and from solar panel. The project is a combination of solar panel, battery, charger controller circuit, power supply circuit, voltage indicator circuit and inverter circuit. Several component which is quite foreign for a student is used in this project, thus required them to learn and observe on how the component work and what is it function. Among the component are integrated circuit (IC) with body code of CD4047, LM 324, and IRZF44 MOSFET. By using several software which are Proteus 7.1, Live Wire, and Circuit Maker software, simulation and printed circuit board (PCB) layout can be conducted. The result obtained from the simulation is recorded and checked whether the circuit is compatible and suitable for completing the project.